Guidance Cue Netrin-1 and the Regulation of Inflammation in Acute and Chronic Kidney Disease - Punithavathi Ranganathan; Riyaz Mohamed; Calpurnia Jayakumar; Ganesan Ramesh (Mediators of Inflammation)
Acute kidney injury (AKI) is a common problem in the hospital setting and intensive care unit. Despite improved understanding, there are no effective therapies available to treat AKI. A large body of evidence strongly suggests that ischemia reperfusion injury is an inflammatory disease mediated by both adaptive and innate immune systems. Cell migration also plays an important role in embryonic development and inflammation, and this process is highly regulated to ensure tissue homeostasis. One such paradigm exists in the developing nervous system, where neuronal migration is mediated by a balance between chemoattractive and chemorepulsive signals. The ability of the guidance molecule netrin-1 to repulse or abolish attraction of neuronal cells expressing the UNC5B receptor makes it an attractive candidate for the regulation of inflammatory cell migration. Recent identification of netrin-1 as regulators of immune cell migration has led to a large number of studies looking into how netrin-1 controls inflammation and inflammatory cell migration. This review will focus on recent advances in understanding netrin-1 mediated regulation of inflammation during acute and chronic kidney disease and whether netrin-1 and its receptor activation can be used to treat acute and chronic kidney disease.